Calcium Signal Pathway is Involved in Prostaglandin E2 Induced Cardiac Fibrosis in Cardiac Fibroblasts - Ma, Yunzi; Yue, Zhongbao; Zhang, Boyu; Yang, Min; Lao, Haiyan; Lai, Weihua; Zeng, Yingtong; Chen, Shaorui; Liu, Peiqing (Journal of Pharmacy & Pharmaceutical Sciences, 2018)
Prostaglandin E2 (PGE2), one of the arachidonic acid metabolites synthetized from arachidonic acid through cyclooxygenase (COX) catalysis, demonstrates multiple physiological and pathological actions through different subtypes of EP receptors. PURPOSE: The present study was designed to explore the effects of PGE2 on cardiac fibrosis and the involved mechanism. METHODS: We used western blot analysis, real-time quantitative PCR and immunostaining etc. to testify the mechanism. RESULTS: Our data showed that in cultured adult rat cardiac fibroblasts (CFs), PGE2 effectively promoted the expression of α-smooth muscle actin (α-SMA), connective tissue growth factor (CTGF)，fibronectin (FN), Collagen I and induced [Ca2+]i increase. Besides, calcium increase evoked by PGE2 is mediated by virtue of EP1 activation. Instead of EP3 or EP4, inhibition of EP1 attenuated PGE2-stimulated upregulation of α-SMA，CTGF, FN, collagen I and [Ca2+]i, as well as the nuclear factor of activated T cell cytoplasmic 4 protein (NFATc4) translocation. CONCLUSIONS: PGE2 may promote cardiac fibrosis via EP1 receptor and calcium signal pathway.